Resistance and resilience to gastro-intestinal nematode parasites and relationships with productivity of Red Maasai, Dorper and Red Maasai X Dorper crossbred lambs in the sub-humid tropics - Baker, R.L.; Nagda, S.M.; Rodríguez Zas, S.L.; Southey, B.R.; Audho, James O.; Aduda, Eric O.; Thorpe, W.R. (Cambridge University Press, 2003)
Resistance and resilience to naturally acquired gastro-intestinal (GI) nematode parasite infections (predominantly Haemonchus contortus) were studied in 1785 lambs born over six lambings (1991 to 1996) consisting of 212 Red Maasai, 311 Dorper and 1262 crossbred (Red Maasai-Dorper) lambs in the sub-humid coastal region of Kenya. These lambs were the progeny of 41 Dorper and 35 Red Maasai rams. Live weights (LWT), blood packed cell volume (PCV) and faecal egg counts (FEC) were recorded at 1- to 2-monthly intervals from birth until the lambs were about one year of age. Red Maasai were more resistant and resilient post weaning to infections with GI nematodes than Dorper lambs as shown by their significantly lower FEC and their significantly higher PCV, respectively. An increasing proportion of Red Maasai genes in the crossbred lambs was associated with decreased FEC and higher PCV, but there was no heterosis for logarithm-transformed FEC (LFEC) or PCFrom one month of age Red Maasai lambs were significantly lighter than Dorper lambs by about 1 kg, but Red Maasai lambs had significantly lower lamb mortality rate from birth to 12 months of age (proportionately 0.30 and 0.66, respectively). Heritability estimates from a repeated measures analysis for records taken at 6 and 8 months of age were 0.14 (s.e. 0.05) for PCV from an animal model and 0.12 (s.e. 0.05) for LFEC from a sire model. The heritability estimate for LFEC from a repeated measures analysis including the four measurements recorded between 6 and 12 months of age was significantly higher (P < 0.05) for Dorper-sired lambs (0.15, s.e. 0.05 for an animal model and 0.19, s.e. 0.07 for a sire model) than for Red Maasai-sired lambs (0.00 and 0.01, s.e. 0.02). The phenotypic and genetic correlations between PCV and LFEC were moderately to highly negative and averaged -0.34 and -0.81, respectively. None of the genetic correlation estimates between LWT and PCV and LWT and LFEC for lambs post weaning were significantly different from zero. The heritability estimates for PCV and LFEC have important implications for within-breed genetic improvement programmes : for the Red Maasai, improvement should concentrate on resilience (e.g. selection for high PCV); for the Dorper, selection should be feasible for both improved resistance (low FEC) and resilience (high PCV).